Implementation of english for specific purposes and communicative approach at Servicio Nacional de Aprendizaje (SENA), branch centro atención sector agropecuario (CASA) in Pereira, Risaralda (2021)
The purpose of this classroom project was to implement an ESP-focused conversation club, develop monitoring sessions and virtual bilingual events at the Servicio Nacional de Aprendizaje (SENA), branch Centro Atención Sector Agropecuario. The participant population was students from different technical and technologist programs offered at this institution ranging from 18 to 35 years old. Recent state tests’ results indicate that, compared to other institutes of similar nature, the SENA presented the largest number of students in the lowest levels of English performance (A1 and A2). Expecting to contribute to the SENA’s efforts to meet the objectives set in its Bilingualism Plan, we strived to provide support in the design and implementation of monitoring sessions of English. Moreover, to foster the communicative competence and the use of technical vocabulary particular to the learners’ field of work, a conversation club took place weekly, where the attendees were able to better their speaking skill while interacting with their peers. After eight months of constant intervention, the apprentices evidenced improvement both in general English and with the lexicon required in the programs they are enrolled in (ESP). Moreover, the execution of two virtual bilingual events expanded the scope of this classroom project, given that more people engaged and benefited from the activities there carried out. An aspect that affected the overall performance of this project was the virtuality since it prevented a stronger teacher-apprentice, apprentice-apprentice interaction, which could have enriched even more the teaching-learning process.